The emergence of the hypervirulent Klebsiella pneumoniae (hvKp) strains among circulating clonal complex 147 (CC147) harbouring bla(NDM/OXA-48) carbapenemases in a tertiary care center of Iran - Pajand, Omid (Ann Clin Microbiol Antimicrob, 2020)
BACKGROUND: Klebsiella pneumoniae is a public health concern because of its ability to develop multidrug resistance and hypervirulent genotypes, of those capsular types K1 and K2 cause community and nosocomial life-threatening infections. This study aimed to determine the antibiotic susceptibility patterns and genotypic traits of a collection of Klebsiella spp. isolates. Furthermore, the clonal relatedness of bla(NDM) producing strains was investigated. METHODS: During a 19-months  surveillance study, 122 Klebsiella spp. isolates were cultured from extraintestinal specimens of patients admitted to the tertiary referral hospital in Semnan, Iran. Isolates were identified using biochemical tests and subjected to determination of phylogroups, capsular types and virulence/resistance genes content. Hypervirulent K. pneumoniae (hvKp) strains were detected genotypically, and Enterobacterial Repetitive Intergenic Consensus (ERIC)-PCR fingerprinting was used to determine the clonality of bla(NDM) producing strains. RESULTS: Multidrug resistant phenotype was detected in 75 (61.5%) isolates and amikacin was found as the most potent antibiotic with the susceptibility rate of 85.2%. The carbapenemase genes were detected in 45 (36.8%) strains, including 21 (17.2%) bla(OXA-48), 7 (5.6%) bla(NDM-1), 14 (11.4%) bla(NDM-1/OXA-48) and 3 (2.4%) bla(IMP-) carrying strains, while 55 (45.08%) isolates showed carbapenem resistant phenotype. The first bla(NDM-1) carrying strain was cultured from a sputum specimen on March 2015, while the last positive one was recovered from blood culture on September 2016. Most of the isolates (80.3%) belonged to phylogroup I, and bla(NDM-1) was identified among all three phylogroups. The ERIC-PCR clustered the 101 bla(NDM) negative and 21 bla(NDM-1) positive isolates into 25 and five clusters, respectively, and the latter group belonged to clonal complex 147 (CC147). One K1 and 15 K2 bla(NDM-1) negative isolates were detected, of those three strains were identified as hvKp. Five K2 positive strains, including four bla(OXA-48) producer and one hvKp sequence type 86 (ST86) were carbapenem resistant. Among carbapenem resistant isolates, CC147 strains harboured higher rates of siderophores iutA and ybtS. CONCLUSION: The present findings showed a hospital circulation of CC147 bla(NDM-1) or bla(NDM-1/OXA-48) producing strains, disseminated in different wards. The hvKp/ST86 strain expressing K2 capsular type and carbapenem resistant phenotype wasn’t reported from Iran so far. So, it seems that we must be aware of the emergence and spread of new K. pneumoniae clones associated with resistant and hypermucoviscous phenotypes.